Airway Management of Esophageal Atresia and Tracheoesophageal Fistula Combined with Anal Atresia. (5th September 2022) - Zhou, Jieshu; Li, Hao; Lin, Xuemei
Abstract : Esophageal atresia (EA) associated with tracheoesophageal fistula (TEF) is a common congenital airway anomaly and may be associated with other gastrointestinal abnormalities. Neonates with EA/TEF are at high risk of gastrointestinal distension due to the shunting of air via the fistula, leading to progressive diaphragmatic elevation and regurgitation of the gastrointestinal contents. EA/TEF associated with anal atresia in a neonate makes airway management even more challenging particularly when managed for the repair of TEF through thoracotomy. Here, we report a case where we succeeded in conducting the flexible bronchoscopy insertion through a laryngeal mask to block the fistula by bronchial blocker under spontaneous breathing.